Peningkatan Efisiensi Penggunaan Air dan Kualitas Tanah Melalui Smart Farming dan Eco-Enzyme di Desa Pancasari Buleleng: Improving Water Efficiency and Soil Quality through Smart Farming and Eco-Enzyme in Pancasari Village, Buleleng - Putri, Putu Indah Dianti; Tapa, I Gede Fery Surya; Yuliandewi, Ni Wayan; Prakasa, I Made Panji Tirta; Wiraatmaja, I Putu Prana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Water efficiency and soil quality are key challenges faced by farmers at Pancasari Village, Buleleng, Bali, particularly in supporting sustainable agricultural practices. This community service project aims to enhance efficiency and sustainability through the implementation of smart farming technology using fertigation channels and the production of eco-enzyme liquid organic fertilizer. The implementation method consists of five stages: problem identification, socialization and education, planning and preparation, training and mentoring, as well as monitoring and evaluation. The results indicate a 30% increase in water efficiency, improved soil fertility with the use of organic fertilizers, and enhanced understanding and engagement of farmers in modern agricultural practices. The evaluation also recorded operational cost savings and increased agricultural productivity. Thus, this project provides effective and sustainable solutions to the challenges faced by farmers, while delivering significant environmental and social benefits.